Allied democratic forces (ADF) in Uganda: A Jihadi- Salafi movement or local political movement in disguise - Nsobya, Abdulhakim Abdalla (Department of Religious Studies, 2019)
Since 1996, Allied Democratic Forces (ADF) has waged a campaign of terror in Uganda and neighbouring Democratic Republic of Congo (DRC), which has resulted in a number of fatalities and continues to threaten the security of the region. From its inception, the objective of the ADF has been to overthrow the Ugandan government and establish an Islamic state governed by a Salafi interpretation of Islam. This study seeks to document the history of the ADF and to locate its position within contemporary Salafi debates. It does so by answering the following questions: (1) what do we know about the ADF? (2) How did the ADF emerge in Uganda? (3) Is the ADF Jihadi-Salafi movement or local political movement in disguise? This study utilises interviews, as well as archival and ethnographic approaches to research. Findings suggest that the ADF is a Jihadi-Salafi militant movement, which was originally established under the name Salafi Jihad Council (SaJiCo). However, the initial failure to stand alone and the Busitema defeat forced them to join other non-Muslim rebel groups to form the Allied Democratic Forces (ADF). In addition, this study confirmed that, persuasive rhetoric of ADF leader, Jamilu Mukulu in addition to a long history of economic, social and political marginalisation of Muslims in Uganda by colonial and post-colonial governments, played a significant role in the creation and recruitment strategies for the Movement.